A narrative review of ai-based digital health policies to enhance nutrition service quality in primary healthcare in Indonesia - Melva Saragi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The rising demand for quality nutrition services and increasing burden of NCDs contrast with Indonesia’s limited adoption of AI in primary healthcare, underscoring the need to explore AI-driven policies to enhance nutrition service delivery in resource-constrained settings. This study examines how AI-based digital health policies can improve the efficiency and quality of nutrition services and identifies barriers that hinder their implementation. A total of 42 articles were reviewed using a framework encompassing three major dimensions: digital system readiness, digital competency of health workers, and robustness of health data governance. The review identified three central challenges: (1) inadequate digital system reliability, which limits the optimal use of AI in primary healthcare facilities; (2) insufficient digital literacy among nutrition personnel and patients, which reduces the effectiveness of AI-based tools; and (3) the absence of clear regulations to ensure health data protection, system interoperability, and ethical AI use. This study contributes new insights by highlighting AI-based nutrition services as an emerging field that requires greater attention in Indonesia’s digital health transformation. The findings underscore the need for stronger policies aimed at enhancing digital infrastructure, improving digital competencies among healthcare workers, and establishing clear regulatory frameworks to ensure the safe and effective use of AI in nutrition services in primary healthcare settings.